1996
DOI: 10.1111/j.1476-5381.1996.tb15201.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in insulin release from rat pancreatic islets by quinolone antibiotics

Abstract: 1 The present study was undertaken to elucidate the mechanism(s) of hypoglycaemia caused by quinolone antibiotics. We investigated the effects of various quinolone antibiotics on insulin release in rat pancreatic islets. 2 At a non-stimulatory concentration of 3 mM glucose, lomefloxacin (LFLX) or sparfloxacin at 1 mM and pipemidic acid (0.1-1 mM) induced slight insulin release but tosufloxacin or enoxacin up to 100 gtM did not. 3 At the stimulatory concentration of 10 mm glucose, all quinolones augmented insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 21 publications
(19 reference statements)
3
77
1
Order By: Relevance
“…Our observation is in apparent contrast to data of Saraya et al [11] who had found a stimulatory effect of 300 µM gatifloxacin or temafloxacin on mouse islets in the presence of 5.5 mM glucose. Similar to our results, Maeda et al [7] found no effect of 100 µM lomefloxacin on rat islets in the presence of a basal glucose concentration (3 mM), but a threefold increase was noted when lomefloxacin was used at the exceedingly high concentration of 1 mM. The glucose dependence of the insulinotropic effect may therefore be a concentration-dependent phenomenon.…”
Section: Characteristics Of Fluoroquinolone-induced Insulin Secretionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our observation is in apparent contrast to data of Saraya et al [11] who had found a stimulatory effect of 300 µM gatifloxacin or temafloxacin on mouse islets in the presence of 5.5 mM glucose. Similar to our results, Maeda et al [7] found no effect of 100 µM lomefloxacin on rat islets in the presence of a basal glucose concentration (3 mM), but a threefold increase was noted when lomefloxacin was used at the exceedingly high concentration of 1 mM. The glucose dependence of the insulinotropic effect may therefore be a concentration-dependent phenomenon.…”
Section: Characteristics Of Fluoroquinolone-induced Insulin Secretionsupporting
confidence: 91%
“…A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 10 view of the slow kinetics of the fluoroquinolones, secretion measurements based on static incubations [7,11] may underestimate the insulinotropic efficacy.…”
Section: Characteristics Of Fluoroquinolone-induced Insulin Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, GFLX was reported to cause dysglycemia (hypoglycemia or hyperglycemia) with much higher frequencies in the retrospective human surveillance [3,15], and particularly diabetes mellitus was considered to be one of the risk factors [6]. In nonclinical investigations, many studies have reported dysglycemia as a consequence of quinolone administration in mice [8] and rats [9] as well as in in vitro studies [13,17,23]. As for GFLX, Saraya et al [17] stated that it stimulated insulin secretion and inhibited -cell ATP-sensitive K + (K ATP ) channel currents in a dose-dependent manner in mouse pancreatic islets.…”
mentioning
confidence: 99%
“…It therefore supports earlier reports claiming that Gatifloxacin causes increased release of insulin leading to hypoglycemia. 9,23,24 …”
Section: Diabetic Rabbitsmentioning
confidence: 99%